Students' satisfaction of the counter service in Office of Academic Affairs of UiTM Kedah / Esnita Usha and Nur Anirah Anuar - Usha, Esnita; Anuar, Nur Anirah (2017)
Service quality practiced by organizations has brought benefits towards the services offered to the customers. In order have an effective and efficient service delivery, service quality can be used as a guideline for the organization. The service quality includes the facilities, responsiveness, assurance and empathy. This study examined the relationship between facilities, responsiveness, assurance and empathy with the students' satisfaction towards the counter service in Office of Academic Affairs of UiTM Kedah. A sample of 242 final year degree students was selected for this study. Stratified random sampling techniques were used. Independent variables and dependent variable hypotheses were proposed for this study to examine the relationship. The result indicates that facilities, responsiveness, assurance and empathy have positive and statistical significant influence towards the students' satisfaction of the counter service in Office of Academic Affairs of UiTM Kedah.